A phase 1/1b study of PUR1900, an inhaled formulation of itraconazole, in healthy volunteers and asthmatics to study safety, tolerability and pharmacokinetics. Issue 4 (16th January 2020) - Hava, David L.; Tan, Lisa; Johnson, Patrick; Curran, Aidan K.; Perry, Jason; Kramer, Steve; Kane, Katie; Bedwell, Pauline; Layton, Gary; Swann, Clarie; Henderson, Dennis; Khan, Naimat; et al.
Abstract : Aims: Oral itraconazole has variable pharmacokinetics and risks of adverse events associated with high plasma exposure. An inhalation formulation of itraconazole (PUR1900) is being developed to treat allergic bronchopulmonary aspergillosis, an allergic inflammatory disease occurring in asthmatics and patients with cystic fibrosis. Methods: A 3‐part, open‐label Phase 1 study was conducted to evaluate safety, tolerability and pharmacokinetics of PUR1900. Healthy volunteers ( n = 5–6/cohort) received either single (Part 1) or multiple (Part 2) ascending doses of PUR1900 for up to 14 days. In Part 3 stable, adult asthmatics received a single dose of 20 mg PUR1900 or 200 mg of oral Sporanox (itraconazole oral solution) in a 2‐period randomized cross‐over design. Itraconazole plasma and sputum concentrations were evaluated. Results: None of the adverse events considered as at least possibly related to study treatment were moderate or severe, and none were classed as serious. The most common was the infrequent occurrence of mild cough. Itraconazole plasma exposure increased with increasing doses of PUR1900. After 14 days, PUR1900 resulted in plasma exposure (area under the concentration–time curve up to 24 h) 106‐ to 400‐fold lower across doses tested (10–35 mg) than steady‐state exposure reported for oral Sporanox 200 mg. In asthmatics, PUR1900 geometric mean maximum sputum concentrations were 70‐fold higher and geometric mean plasma concentrations were 66‐fold lower than with oral Sporanox. Conclusion: PUR1900 was safe and well‐tolerated under the study conditions. Compared to oral dosing, PUR1900 achieved higher lung and lower plasma exposure. The pharmacokinetic profile of PUR1900 suggests the potential to improve upon the efficacy and safety profile observed with oral itraconazole.